التعليم العالي الاهلي في العراق والاتجاهات العربية والعالمية في تمويل التعليم العالي - هاشم الملاح; بسمان فيصل محجوب (PROSPECTIVE RESEARCHES, 2023)
This research presents a summary of the evolution of private education in Iraq in regard to its financing, its relationship will the official higher education in Iraq, and the development of this relationship through different stages. The study also presents an analysis to the difficulties and challenges that face the private education nowadays. In the hope of finding some remedial measures to this situation, the research sheds light on some Arabic experiences that enriches this field. So that we can get some recommendations which may be helpful in overcoming the challenges which might face the private higher education in Iraq.